2015
DOI: 10.1057/dddmp.2015.18
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting consumer usage of QR codes

Abstract: In recent years, various institutions have adopted the use of twodimensional bar codes, also known as QR (quick response) codes, for encoding information such as URLs that can be read by smartphones, digital tablets and other electronic devices. These codes can serve as a vehicle to evoke a consumer response or some type of behaviour. Their main benefit is that users of smartphones are alleviated from the tedious task of typing and searching to access information. This paper provides the results of a survey st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…However participants who showed interest in QR codes were highly likely to use them in the future. Similar results were obtained in more recent work (Ozkaya et al, 2015, Lo, 2014 which also found that even individuals who considered themselves innovative were not very likely to use QR codes.…”
Section: Qr Code Adoptionsupporting
confidence: 88%
“…However participants who showed interest in QR codes were highly likely to use them in the future. Similar results were obtained in more recent work (Ozkaya et al, 2015, Lo, 2014 which also found that even individuals who considered themselves innovative were not very likely to use QR codes.…”
Section: Qr Code Adoptionsupporting
confidence: 88%
“…Today, consumers are familiar with QR codes and NFC, but they are not willing to read them regularly using their mobile phones; they feel that they do not get any additional value from it. It is essential that the consumers trust the service and service provider [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Before the COVID-19 pandemic, an earlier exploratory study reported that the familiarity with QR codes was low among college students (44%) and only 68% used them for seeking information and purchasing, suggesting the novelty of the QR codes attributing to the low awareness levels (Ozkaya et al, 2015). Nevertheless, during the pandemic, the availability of the QR codes increased exponentially with the creation of NHS QR codes for hospitality industries, tourism and leisure centres, libraries and community centres (Department of Health and Social Care, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Approval was granted from the Quality Control and Governance Team on 27 August 2020. Our sample size was based on a previous study that recruited 79 participants assessing QR code familiarity and usage (Ozkaya et al, 2015). Post hoc statistical power analysis was also conducted assuming a null hypothesis of the proportion of patients using the QR code is 0.5, difference of 0.65, a significance of α = 0.05 and a power of 0.9, giving a sample size of 107.…”
Section: Methodsmentioning
confidence: 99%